Analisis bibliometrik penelitian tentang perpustakaan digital di Indonesia tahun 2013-2024. - Zahidah Sabilillah; Rully Khairul Anwar; Yunus Winoto (FPPTI Jawa Tengah, 2024)
This study aims to analyze the development of research on digital libraries in Indonesia from 2013 to 2024 using a bibliometric analysis approach. Using data indexed in Scopus, this study evaluates the trends of scientific publications, the contribution of lead authors, as well as the development of the concept of digital literacy in the context of digital libraries. Bibliometric methods were used to provide greater insight into the direction and evolution of research in this area, as well as to identify emerging patterns in the related literature. The results show that despite the significant growth in the number of publications on digital libraries, the main challenges faced include infrastructure gaps, limited human resources, as well as data security issues that still need serious attention. In addition, despite the rapid development of technology, the unequal distribution of access is an obstacle in expanding the benefits of digital libraries. This research is expected to make a positive contribution to the development of digital literacy policies and practices in Indonesia, as well as encourage increased access to higher quality and relevant information. With these findings, it is also expected to accelerate efforts to improve digital library services, making them more accessible to all levels of society, and strengthening the digital literacy ecosystem in the country.